Brief Historical Study of Environmental Thought. Review of Environmental Thought: A Short History by Robin Attfield - Sayem, Md. Abu (Studia Ecologiae et Bioethicae, 2025)
The article outlines the historical development of environmental thought from ancient to postmodern times, analyzing how humanity's relationship with nature has evolved. Initially shaped by theocentric worldviews where nature was seen as sacred and humans as stewards, environmental perception shifted drastically during the Renaissance and modern periods with the rise of materialism and mechanistic science. Thinkers like Descartes and Bacon reduced nature to mere matter, legitimizing exploitation. However, with modern biology and ecological awareness, a biocentric and ecocentric shift reemerged, recognizing interdependence among all living beings. Postmodern thinkers have begun advocating for environmental ethics and sustainability, although consumerist lifestyles continue to hinder progress. The text critiques the author's limited coverage of non-Western perspectives, particularly those from Asia and Africa, and calls for a more inclusive and chronological approach.